1974
DOI: 10.1159/000240632
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine Dystrophy in Rats Due to Placental Insufficiency Caused by Hormonally Induced Prolonged Gestation

Abstract: The duration of pregnancy in rats can be prolonged beyond day 26 after conception by administration of synthetic gestagens. The fetal mortality increased with prolonged duration of gestation to 24.8% on day 24 and 54.6% on day 25. Nearly all the fetuses were dead on day 26. On day 24 some of the litter mates and on day 25 all of the living ones were markedly hypotrophic. A placental insufficiency is suggested as causing the increasing mortality and the hypotrophy of the fetuses. The placental weight increases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1975
1975
2006
2006

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Concomitant with this reduction, the rate of fetal growth, as indicated by changes in fetal body weight, is also reduced. Similar findings on placental and fetal weight during prolonged gestation in the rat have been already reported by Buhrdel et al (2). Present data does not provide a clear explanation as to the mecha nisms involved in these effects.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Concomitant with this reduction, the rate of fetal growth, as indicated by changes in fetal body weight, is also reduced. Similar findings on placental and fetal weight during prolonged gestation in the rat have been already reported by Buhrdel et al (2). Present data does not provide a clear explanation as to the mecha nisms involved in these effects.…”
Section: Discussionsupporting
confidence: 79%
“…After prolonged gestation the fetuses are gener ally bom showing signs of nutrient deficiency (2,3). These phenomena have been interpreted by many as caused by placental aging.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, histochemical studies by Kaufmann and Stark (9) on human term placentas revealed a marked reduction in placental enzymes in areas of syncytial necrosis and fibrinoid deposition. In experimentally induced prolonged gestation in rats and rabbits, placental insufficiency resulted in depletion of fetal hepatic glycogen stores, fetal hypoglycaemia and hypoxia and increase in mortality (1,8,(17)(18)(19). A reduction in hepatic glycogen and blood glucose levels is also frequently observed in human 'small-for date' infants subjected to intra-uterine growth retardation (18).…”
Section: Discussionmentioning
confidence: 99%
“…Studies with newborn rats at gestational ages of 21 and 25 days did not succeed due to the high mortality rate of the preterm and postterm rat babies. When gestation is prolonged by hormonal action, fetal growth is impaired by deficient intrauterine nutrition due to placental insufficiency (10) which also causes increases in intrauterine mor tality rate (4). According to recent studies (2, 3), a direct effect of the gestagen on the fetus is unlikely.…”
Section: Discussionmentioning
confidence: 99%